Outcomes of 25-gauge pars plana vitrectomy with encircling scleral band for acute retinal necrosis-related rhegmatogenous retinal detachment - Bruttendu Moharana (Indian Journal of Ophthalmology, 2021)
Purpose: The aim of this study was to evaluate the anatomic and functional outcomes of 25-gauge pars plana vitrectomy (25G PPV) with encircling scleral band (ESB) in patients with acute retinal necrosis (ARN)-related rhegmatogenous retinal detachment (RRD). Methods: Single-center retrospective interventional case series of patients who underwent 25G PPV with ESB for ARN-related RRD. Complete anatomic success was defined as the complete attachment of retina after primary PPV. Functional success was measured by the final best-corrected visual acuity (BCVA) ≥20/400. Intraoperative and postoperative complications were also noted. Results: 14 eyes of 13 patients were included in the study. Six patients (46.1%) were immunocompromised. The mean follow-up was 23.64 ± 9.95 (range 6-42) months. Silicone oil was used as tamponade in 13 eyes and C3F8gas in one eye. After the primary PPV, complete anatomical success was seen in all eyes (100%), however, one eye developed phthisis bulbi after silicone oil removal (SOR). Statistically significant improvement of BCVA was seen, from LogMAR 2.03 ± 0.29 preoperatively to LogMAR 1.57 ± 0.63 postoperatively (p-value 0.014). Six eyes (42.9%) had functional success. Nine eyes (64.3%) had improvement in vision while 4 eyes (28.6%) maintained preoperative vision. 10 eyes (71.4%) underwent cataract surgery, nine eyes (64.3%) underwent SOR while 2 eyes (14.3%) had epiretinal membrane (ERM) under oil during follow-up. Conclusion: 25G PPV combines the advantages of minimally invasive vitrectomy surgery while offering improved anatomic outcomes in patients with ARN-related RRD. The functional outcome varies depending on the status of the optic disc and macula.